Post-Fire Effects in Wetland Environments: Landscape Assessment of Plant Coverage and Soil Recovery in the Paraná River Delta Marshes, Argentina - Salvia, María Mercedes; Ceballos, Dario Sebastian; Grings, Francisco Matias; Karszenbaum, Haydee; Kandus, Patricia (Springer, 2019)
During 2008, under a region-wide drought, there were a large number of simultaneous fires in the Paraná River Delta region: the most affected vegetation was in marshes dominated by Schoenoplectus californicus (C.A.Mey.) Soják or Cyperus giganteus Vahl. The objective of this paper was to study fire severity in terms of fire effect on vegetation cover and soil properties, and the recovery of those properties after one growing season, using optical remote sensing techniques and fieldwork data. To this aim, we performed unsupervised classification of Landsat TM imagery and conducted vegetation censuses and soil sampling in November 2008 and May 2009. Our results show that we could identify three fire severity classes: low severity, medium severity, and high severity. These classes are characterized by a remnant vegetation cover of approximately 75 %, 25 %, and 5 %, respectively, and a diminution of soil organic carbon and nitrogen of 66 % and 59 % in the case of medium severity and high severity. Fire had almost no effect over pH and a slight effect on electrical conductivity. After one growing season, vegetation recovery is dependent on fire severity and hydrological condition, while soil properties did not show signs of recovery. This is one of the first studies of fire effects and recovery on fluvial herbaceous wetlands.